2020
DOI: 10.3390/jcm9082680
|View full text |Cite
|
Sign up to set email alerts
|

Application of Anti-Inflammatory Agents in Prostate Cancer

Abstract: Chronic inflammation is a major cause of human cancers. The environmental factors, such as microbiome, dietary components, and obesity, provoke chronic inflammation in the prostate, which promotes cancer development and progression. Crosstalk between immune cells and cancer cells enhances the secretion of intercellular signaling molecules, such as cytokines and chemokines, thereby orchestrating the generation of inflammatory microenvironment. Tumor-associated macrophages (TAMs) and myeloid-derived suppressor c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 300 publications
(305 reference statements)
0
13
0
Order By: Relevance
“…Studies conducted in in vitro and in animals demonstrated that metformin inhibits PCa cell proliferation, migration, and progression by activating AMPK and blocking mammalian target of rapamycin (mTOR) complex 1 signaling [ 84 95 ], by blocking cell cycle in G 0 /G 1 through a decrease of cyclin D1 level [ 96 ], by inhibiting the forkhead box M1 transcription factor and thus suppressing EMT [ 97 ], by inhibiting androgen receptor [ 68 ], by inhibiting tumor-associated inflammatory infiltration [ 98 ], through up-regulation of pigment epithelium-derived factor [ 99 ], by suppressing the expression of enhancer of zeste homolog 2 (EZH2) via upregulating miR-26a-5p [ 100 ], by downregulating the c-myc oncogene [ 101 ], by inhibiting the IGF-1 pathway and via many other potential molecular pathways which have been extensively reviewed by other investigators [ 102 103 104 ]. The anti-neoplastic activity of metformin on PCa could be enhanced by the combination use with rapamycin [ 95 ], 2-deoxyglucose [ 105 ], simvastatin [ 106 107 ], doxorubicin [ 108 ], an inhibitor of polo-like kinase 1 [ 109 ], valproic acid [ 110 ], GSK126 (an inhibitor of EZH2) [ 100 ], exendin 4 [ 111 ], aspirin [ 112 ], or solamargine (a major steroidal alkaloid glycoside) [ 113 ].…”
Section: Prostate-related Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies conducted in in vitro and in animals demonstrated that metformin inhibits PCa cell proliferation, migration, and progression by activating AMPK and blocking mammalian target of rapamycin (mTOR) complex 1 signaling [ 84 95 ], by blocking cell cycle in G 0 /G 1 through a decrease of cyclin D1 level [ 96 ], by inhibiting the forkhead box M1 transcription factor and thus suppressing EMT [ 97 ], by inhibiting androgen receptor [ 68 ], by inhibiting tumor-associated inflammatory infiltration [ 98 ], through up-regulation of pigment epithelium-derived factor [ 99 ], by suppressing the expression of enhancer of zeste homolog 2 (EZH2) via upregulating miR-26a-5p [ 100 ], by downregulating the c-myc oncogene [ 101 ], by inhibiting the IGF-1 pathway and via many other potential molecular pathways which have been extensively reviewed by other investigators [ 102 103 104 ]. The anti-neoplastic activity of metformin on PCa could be enhanced by the combination use with rapamycin [ 95 ], 2-deoxyglucose [ 105 ], simvastatin [ 106 107 ], doxorubicin [ 108 ], an inhibitor of polo-like kinase 1 [ 109 ], valproic acid [ 110 ], GSK126 (an inhibitor of EZH2) [ 100 ], exendin 4 [ 111 ], aspirin [ 112 ], or solamargine (a major steroidal alkaloid glycoside) [ 113 ].…”
Section: Prostate-related Healthmentioning
confidence: 99%
“…Chronic inflammation resulting from prostatitis, BPH, or other etiologies may promote the development of PCa and is a promoter of metastasis and therapeutic resistance in PCa [ 78 80 81 ]. The use of metformin as an anti-inflammatory agent in the management of PCa has also been proposed [ 103 104 ].…”
Section: Prostate-related Healthmentioning
confidence: 99%
“… 11 The gut microbiota is also strongly influenced by dietary habits and body shape, 12 , 13 and is involved in host inflammation and immune responses. 14 We have previously shown in animal studies that a high‐fat diet and obesity promote local prostate inflammation and PCa proliferation, 15 , 16 , 17 , 18 and that SCFAs, major metabolites of intestinal bacteria, promote PCa growth via the IGF‐1 signaling pathway. 19 These findings suggest that the gut microbiota, altered by diet and other external factors, may be involved in PCa progression through multiple mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…The broad use of statins as first-line therapeutics for prevention of cardiovascular disease by inhibition of cholesterol synthesis raised the possibility of their effect on PCa. Findings from several studies indicate that statins may also play a role as anti-cancer agents in PCa via both cholesterol and pleiotropic non-cholesterol-mediated effects [ 108 , 114 , 115 , 116 , 117 , 118 ]. In preclinical settings, simvastatin and lovastatin have been found to reduce cell viability through an induction of apoptosis; to inhibit cell proliferation, colony formation, and migration; to suppress the AKT pathway; and to cause G 1 phase cell cycle arrestation in AR-positive LNCaP, AR-negative PC-3, and DU145 cells, while atorvastatin, simvastatin, and rosuvastatin have all been shown to reduce the metastatic potential of PC-3 cells [ 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 ].…”
Section: Effect Of a Class Of Drugs That Inhibit Cholesterol Synthesis On Prostate Cancer (Pca)mentioning
confidence: 99%